Optimalisasi Pengoperasian Pipa Minyak Mentah Jalur Minas-Duri dengan Lean Sigma - Denny Astrie Anggraini; Rita Kusrina (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
As a business unit of oil and gas companies operating in Riau, in distributing the products, the company uses the pipeline that carries crude oil from Gathering to Terminal. One of the segments of pipe used is from North Booster Pump (NBS) Minas to Pungut that uses 2 pieces of carbon steel pipe with a diameter of 30" and 26" and forwarded to Duri with 1 piece of pipe 30". With this condition utilization of two pipes become waste due to operational and maintenance costs be high, the company wanted to review the use of the pipeline to be optimal. This study provides recommendations to companies with Lean Sigma method study on the use of the pipeline. Considerations in providing recommendations to, include factors of production capacity, the capacity of the pipeline and the costs incurred. So given the recommendation to use 1 line of the pipeline 30" with the level of effectiveness of 94% from the previous 54%. Prior to implementation in the field, pressure pipe applications SimSci PIPEPHASE simulated. And with 1 piece of the pipeline company can save expenditure of 858.765 US $ per year.Keywords: cost, Lean Sigma, optimization, pipeline, waste